Zdravstvena vzgoja bolnikov s sladkorno boleznijo v Splošni bolnišnici Ptuj - Klampfer, Suzana (Obzornik zdravstvene nege, 2002)
The most important segment of nurse's work in outpatients' department for diabetes in Ptuj General Hospital is health education of patients with diabetes, without which the nurses could not imagine their work in educating patients. The article in research presents diet habits of diabetes patients inthe area of Ptuj and Ormož. It also shows a reasonable amount of perception and accomplishment of patients with diabetes.
Keywords: ankete; Bolnik, izobraževanje; bolniki; Diabetes Mellitus; Hospitalizacija; Hospitalization; medicinske sestre; Nursing; Patient Education; Questionnaires; Sladkorna bolezen; zdravstvena vzgoja